Clinical manifestations and treatment of mucopolysaccharidosis type i patients in Latin America as compared with the rest of the world (2011)
Background Mucopolysaccharidosis I (MPS I) comprises a spectrum of clinical manifestations and is divided into three phenotypes reflecting clinical severity: Hurler, Hurler- Scheie, and Scheie syndromes. There may be important variations in clinical manifestations of this genetic disease in patients residing in different regions of the world. Methods Using data from the MPS I Registry (as of September 2009), we evaluated patients from Latin America (n=118) compared with patients from the rest of the world [ROW (n=727)]. Results Phenotype distribution differed among patients in Latin America compared to ROW(Hurler 31 vs. 62%, Hurler- Scheie 36 vs. 21%, Scheie 10 vs. 11%, and unknown 22 vs. 6%). The frequency of certain symptoms, such as cardiac valve abnormalities, sleep impairment, and joint contractures, also differed between Latin America and ROW for some phenotypes. Median age at MPS I diagnosis was earlier in the ROW than Latin America for all phenotypes, and age at first treatment for Hurler and Hurler-Scheie patients was also earlier in the ROW. Hurler patients in Latin America showed a gap of 3.1 years between median ages of diagnosis and first treatment compared to only 0.5 years in the ROW. Treatment allocation in Latin America compared to ROW was as follows: enzyme replacement therapy (ERT) only, 80 vs. 45%; hematopoietic stem cell transplantation (HSCT) only, 0.9 vs. 27%; both ERT and HSCT, 0 vs. 16%; and neither treatment, 19 vs. 13%. Conclusion These data highlight important differences in MPS I patients between Latin America and ROW in terms of phenotypic distribution, clinical manifestations, and treatment practices. © The Author(s) 2011.